Enhancing The Speaking Performance Of Efl College Students Through Video Projects - Hasanah, Yuli Astuti; Pradana, Satria Adi Adi (Universitas Islam Negeri Raden Intan Lampung, 2019)
The study described how video projects were used to enhance the speaking performance of EFL college students in IAIN Kediri, Indonesia. The researcher found that students faced technical and personal problems appeared in the speaking class. A classroom action research was applied to the study to solve the problems. Then, the data was analyzed descriptively. The result of the study identified that students emerged confidence, fluency, good collaboration and excitement in the speaking class. The study resulted that obstacles of speaking English can be solved alternatively through the used of song videos as the project by practicing the aspects of the language in song lyrics and producing videos which then were spread out through YouTube website in order to appreciate their work and creativity as well as to share it as useful sources of teaching media and also entertainment.